Organisational capabilities and competitive advantage: the moderating effects of managerial competencies in processed foods SMEs in Malaysia / Nurul Nadia Abd Aziz - Abd Aziz, Nurul Nadia (Institute of Graduate Studies, UiTM, 2017)
The premise of this research is that the SMEs in Southeast Asia, including Malaysia, are facing difficulties to survive. Recently, some scholars have argued that the SMEs in Malaysia have a lack of competitiveness regarding costs, products and services. Thus, this study aims to provide a better understanding of continuous knowledge sharing by determining; (1) the effects of organisational capabilities on competitive advantage among the food processing SMEs in Malaysia; and (2) the relationship between innovation, networking, financial capabilities, and competitive advantage. Furthermore, this study incorporates knowledge and skills as a moderating variable, renamed as managerial competencies which possibly strengthen the likelihood that strong organisational capabilities may lead to competitive advantages. Therefore, this study also aims to determine the moderating effects of managerial competencies on the relationship between organisational capabilities and competitive advantage. A random sampling technique was applied to collect the data from 2,384 SMEs processing food products in Malaysia. A total of 330 SMEs in the food processing industry had participated in this study. The main instrument for this study is a set of questionnaire which was adopted from previous studies. A structural equation modelling using AMOS was applied in analysing the direct and moderating effect hypotheses…